2008
DOI: 10.1016/j.apnu.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision Making and Serious Mental Illness

Abstract: This study examined medication decision making by 84 persons with serious mental illness, specifically examining relationships among perceived coercion, decisional capacity, preferences for involvement and actual participation, and the outcomes of medication adherence and QoL. Multiple and logistic regression analysis were used in this cross-sectional, descriptive study, controlling for demographic, socio-economic and utilization variables. Appreciation was positively related to medication adherence behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…Some of them could be applied to our findings. First, patients' health worldview, including health belief models, treatment preferences, involvement of family, greater trust in their physician and attitude may vary and influence a patient's preference for participation (influence by cultural attitudes and tradition) [37][38][39][40]. Second, perceived lack of knowledge, lack of self-efficacy or a learned response influenced by cultural attitudes may contribute to this as well [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them could be applied to our findings. First, patients' health worldview, including health belief models, treatment preferences, involvement of family, greater trust in their physician and attitude may vary and influence a patient's preference for participation (influence by cultural attitudes and tradition) [37][38][39][40]. Second, perceived lack of knowledge, lack of self-efficacy or a learned response influenced by cultural attitudes may contribute to this as well [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Mahone (2008) Loh, Leonhart et al (2007) found a significant positive relationship (by the Patient Participation Scale from Man-Son-Hing (MSH-scale)). Tambuyzer & Van Audenhove (2015), Golnik, Maccabee-Ryaboy et al (2012) and Swanson et al (2007) observed that perceived SDM significantly predicted patients' (or parents') satisfaction with care.…”
Section: Sdm Antecedentsmentioning
confidence: 99%
“…39,[69][70][71] In addition, participants in a number of studies declared that they had a clear desire for greater participation in decision regarding their psychiatric care compared to the current care they were receiving. 39,65,67,70 To illustrate, in one study, 82 percent of participants preferred a collaborative relationship with their health care provider, however only 70 percent experienced this collaboration. 65 Interestingly, participants articulated a clear idea of how and when to prioritise autonomy in decision-making and when to consult or defer the decision to health care professionals.…”
Section: Preferences In Decision-makingmentioning
confidence: 99%
“…Some authors have found that shared decision-making interventions had some impact on reducing the severity of substance-related and/or psychiatric problems but did not impact quality of life. 64,65 Another study found shared decision-making to have a significant impact for clients with a mental illness even when deciding on secondary decisions like lifestyle behaviours. 66 Mahone (2008) found that participation in shared decision-making was associated with better medication adherence rates, 65,67 while a recent study found that a computerized shared decision-making tool had no impact on medication adherence in community outpatient settings.…”
Section: Shared Decision Making In Mental Health Carementioning
confidence: 99%